2008
DOI: 10.2474/trol.3.100
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Analysis of the Tribochemical Reaction of CNx by FTIR

Abstract: Carbon Nitride (CNx) coating was reported to show a superlow friction coefficient when it slid against a Si 3 N 4 ball in nitrogen gas at atmospheric pressure. This superlow friction phenomenon occurred after a number of sliding cycles, in the so-called running-in period, due to the nitrogen atom desorption from the topmost CNx coating surface; its the surface became a graphite-like layer, and a transfer layer was formed on the counter material surface. However, a friction test and surface analysis should be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…These results are considered as a sign that the chelating molecule effectively forms complexes, demonstrating successful synthesis, and serve as strong confirmation of this conclusion. The appearance of peaks at 1970, 1342, and 1105 cm −1 , which are attributed to N=C [ 36 , 37 ], S=O [ 38 , 39 , 40 , 41 ], and C-N [ 42 , 43 ], respectively, indicates that HQS was adsorbing, which was likely prompted by the emergence of an organic film covering the LDH architecture. Figure 3 b provides additional evidence for the existence of the organic self-assembly on the layered coating material.…”
Section: Resultsmentioning
confidence: 99%
“…These results are considered as a sign that the chelating molecule effectively forms complexes, demonstrating successful synthesis, and serve as strong confirmation of this conclusion. The appearance of peaks at 1970, 1342, and 1105 cm −1 , which are attributed to N=C [ 36 , 37 ], S=O [ 38 , 39 , 40 , 41 ], and C-N [ 42 , 43 ], respectively, indicates that HQS was adsorbing, which was likely prompted by the emergence of an organic film covering the LDH architecture. Figure 3 b provides additional evidence for the existence of the organic self-assembly on the layered coating material.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a carbon nitride (CN x ) coating, which is a type of DLC coating containing nitrogen in the carbon structure, has attracted significant attention because it can achieve low friction behavior and high wear resistance under unlubricated conditions in inert environments [13]. CN x coatings exhibit a low friction coefficient of less than 0.05 sliding against CN x or Si 3 N 4 under inert gas-blowing conditions or atmospheres (Ar, He, or N 2 gas) [14][15][16][17][18][19][20][21][22][23]. Wang et al and Watari et al reported that an invisible carbonaceous tribolayer with a nanometerordered thickness (approximately 10 nm or less), which has a carbon structure graphited from the initial structure of the coatings, was formed on the mating material when CN x coatings exhibited such low friction [14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Coatings provide superior surface properties due to high-performance materials while reducing the cost of the application using inexpensive substrates. In recent years, diamondlike carbon (DLC) coatings have attracted attention as new carbonaceous hard coatings due to their high hardness, chemical inertness, and low-friction properties. Moreover, many characteristics (e.g., surface energy, friction properties, and oiliness) can be controlled by doping with other elements (e.g., nitrogen, silicon, boron, and fluorine). Therefore, DLC coatings already have many industrial applications (e.g., molds, piston rings, and drills). Recently, it is revealed that a type of hard DLC coatings, tetrahedral amorphous carbon (ta-C), and nitrogen-doped ta-C (ta-CNx) have excellent thermal stability and high wear resistance due to a high fraction of carbon sp 3 orbital bonding. Therefore, these coatings are considered next-generation functional coatings.…”
Section: Introductionmentioning
confidence: 99%